Needs of persons with disabilities for competences that expand employment opportunities in the conditions of society digitalisation - V. N. Kozlov; D. F. Romanenkova (Цифровая социология)
The article examines the needs of students and graduates of universities from among persons with disabilities in additional professional competencies necessary for successful employment in the context of the society digitalisation. The empirical base was the materials of a survey on a representative sample of 140 final year students and graduates with disabilities from the Sverdlovsk, Chelyabinsk and Kurgan regions. As a result, professional competencies were identified that expand their employment opportunities for people in this category: practical professional skills; professional knowledge in the subject area; digital competencies and information technology skills; the ability to work in the media space, including social networks; knowledge of interaction technologies, self-presentation and effective communication; the ability to tell a wide audience about their services, skills, about themselves as a specialist; the ability to promote themselves, their professional competencies and services. The authors of the article substantiate the need to obtain such competencies within the framework of additional professional education. It has been established under what conditions graduates and students with disabilities are ready to receive the additional professional education they need, how the assessments of these competencies differ in groups according to the formation of competencies, employment, disability, types of health disorders and gender. The results of this study indicate the importance of digital competencies for persons with disabilities in current conditions, they are significant for further study of this problem, the implementation of additional professional education programmes.